Respuesta :
Answer:-730b^2-1404b-16
Step-by-step explanation:
11b^2-4b+711b2-4b+711b^2-4b+7=
(11+711)b^2+(-4+711.2-4-4)b+7= 722b^2+1410b+7 =A
b^2+8b-9b2+8b-9b^2+8b-9=
(1-9)b^2+(8-9.2+8+8)b-9= -8b^2+6b-9 =B
B-A= (-8-722)b^2+(6-1410)b+(-9-7)= -730b^2-1404b-16
Answer:
[tex]-10b^2+12b-16[/tex]
Step-by-step explanation:
Consider the given question is " Subtract [tex]11b^2-4b+7[/tex] from [tex]b^2+8b-9[/tex]".
[tex](b^2+8b-9)-(11b^2-4b+7)[/tex]
Using distributive property we get
[tex]b^2+8b-9-(11b^2)-(-4b)-(7)[/tex]
[tex]b^2+8b-9-11b^2+4b-7[/tex]
On combining like terms we get
[tex](b^2-11b^2)+(8b+4b)+(-9-7)[/tex]
[tex]-10b^2+12b+(-16)[/tex]
[tex]-10b^2+12b-16[/tex]
Therefore, the resultant expression is [tex]-10b^2+12b-16[/tex].